Strengthening MSME Competitiveness through Halal Certification Assistance: A Community-Based Development Approach in Botoputih Village - Luluk Indarti; Mohammad Ja’far As-Shodiq; Muhamad Hasan Abdillah (LP2M Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Purpose: This service program aims to strengthen the legality and competitiveness of MSME products in Botoputih Village, Bendungan District, Trenggalek Regency through halal certification assistance. A total of 101 businesses were reached, with 107 products successfully registered for certification, highlighting the program’s significant impact. Method: The program applied the Asset-Based Community Development (ABCD) approach, which emphasizes utilizing local potential through four stages: discovery, dream, design, and destiny. Practical Applications: The activities were implemented through socialization, field surveys, door-to-door visits, and technical assistance in using the Sihalal platform. This program provided education on legality, increased awareness of halal certification, and fostered a culture of compliance among local entrepreneurs. Conclusion: The results demonstrate that participatory and educative approaches are effective in increasing the capacity of local business actors, ensuring product legality, and supporting sustainable empowerment of MSMEs in rural areas.